Front Cover: Three in One: The Versatility of Hydrogen Bonding Interaction in Halide Salts with Hydroxy‐Functionalized Pyridinium Cations (ChemPhysChem 18/2021). Issue 18 (15th September 2021) - Al Sheakh, Loai; Niemann, Thomas; Villinger, Alexander; Stange, Peter; Zaitsau, Dzmitry H.; Strate, Anne; Ludwig, Ralf
Abstract : The Front Cover shows one of the three types of hydrogen bonding observed in hydroxy‐functionalized halide salts. Here, the halide anion forms a hydrogen bond to the hydroxy group and interacts with the ring system of the cation at the same time. The versatility of structures demonstrates the importance of non‐covalent interactions, in particular the role of hydrogen bonding. More information can be found in the Communication by Ralf Ludwig and co‐workers .